PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lubis, Desiyusliani; Siregar, Liper; Jubi, Jubi; Astuti, Astuti (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The purpose of this research is to know the description of leverage, profitability and firm’s value and to determine influence of leverage and profitability to the firm’s value at Firm in Chemical Sub-Sector listed on the Indonesia Stock Exchange. The research design used in this research is library research. The analysis data technique used in this research are assumption classic test, qualitative and quantitative descriptive analysisThe result shown Ŷ = -0,055 + 1,502X1 + 6,689X2.,  Correlation coefficient of r = 0,463 and Rvalue of 0,214. The simultaneous test results Fcount>Ftable (5,051 > 3,25) or significant level obtained 0,011 < 0,05 means leverage and profitability have significant effect on the firm’s value at Firm in Chemical Sub-Sector listed on the Indonesian Stock Exchange. The t-test results show leverge has tcount>ttable (2,162 > 2,02619) or significance level 0,037 < 0,05, means leverage has significant effect on firm’s value at Firm in Chemical Sub-Sector listed on the Indonesian Stock Exchange. The t-test results that profitability to tcount>ttable (3,134 > 2,026) or significance level 0,003 < 0,05, means profitability has significant effect on firm’s value at Firm in Chemical Sub-Sector listed on the Indonesian Stock Exchange.The result of this research suggests management  companies should still optimize the use of corporate funds and increase sales. And for the next researchers should use or add to other research variables. Keywords: Leverage, Profitability, and Firm Value